Principles of good practice in SoTL - Felten, Peter (Teaching and Learning Inquiry, 2013)
For the Scholarship of Teaching and Learning (SoTL) to be understood as significant intellectual work in the academy, SoTL practitioners need to identify shared principles of good practice. While honoring the diversity of SoTL in its many forms across the globe, such principles can serve as a heuristic for assessing work in our field. These principles include (1) inquiry into student learning, (2) grounded in context, (3) methodologically sound, (4) conducted in partnership with students, and (5) appropriately public. Taken together, these five principles can be guideposts for developing and refining individual SoTL inquiries and larger SoTL initiatives. These principles also can clarify and demystify SoTL to those on our campuses who evaluate our work, helping us to make the case for institutional resources and support for SoTL. Even more importantly, these principles articulate a vision of a scholarship that enhances, perhaps even transforms, teaching and learning in higher education.